Strain Path Influence on Formability and Microstructural Evolution of IFHS Steel via Miniature LDH Test - Kumar Pavan; Mahajan Peeyush; Mishra Sushil K.; Datta Rahul; Narasimhan K. (MATEC Web of Conferences)
This work investigates effect of strain path on the forming behaviour and microstructural evolution of Interstitial Free High Strength (IFHS) steel using miniature Limiting Dome Height (LDH) test. Miniature samples representing uniaxial, plane strain, and biaxial conditions were fabricated from 0.7 mm thick IFHS steel sheets and deformed up to necking using the miniature LDH test to generate Forming Limit Diagram (FLD). The microstructural changes occurred along different strain paths were analysed on deformed miniature samples using Electron Backscattered Diffraction (EBSD) and X-ray Diffraction (XRD) techniques. IPF map showed almost similar level of deformation in the neck and near neck region of the plane strain sample. In case of uniaxial and biaxial samples high fraction of non-indexed zone were noted in the neck region compare to the near neck region due to the localized deformation. Texture analysis revealed higher ‘BRASS’ and ‘GOSS’ intensities in the neck region of uniaxial specimens, indi cating greater deformation. Biaxial specimens at neck and near neck region showed ‘RCUBE’ rotation to ‘CUBE’ texture, enhancing isotropy for better formability. In case of plane strain sample textures such as ‘COPPER’, ‘BRASS’, and ‘S’ were notably low, likely due to reduced strain levels in the deformation mode.